The role of dendritic cells in MASH: friends or foes? - Pinto, Antonio T.; Lukacs-Kornek, Veronika (Frontiers in Immunology, 2024)
Dendritic cells (DCs) are the major antigen presenting cells that connect innate and adaptive immunity. Hepatic DCs are less activated and contribute to maintain the tolerogenic environment of the liver under steady state. Several studies indicated DCs in Metabolic Dysfunction Associated Steatohepatitis (MASH) that represent a substantial burden on healthcare systems due to its association with liver-related morbidity and mortality. Studies highlighted the potential disease promoting role of liver DCs in the development of MASH while other experimental systems suggested their protective role. The review discusses this controversy and the current understanding of how DCs affect the pathogenesis of MASH.